Cardiopulmonary Exercise Testing in Patients with Post-COVID-19 Syndrome - Barbagelata, Leandro; Masson, Walter; Iglesias, Diego; Lillo, Ezequiel; Migone, Juan Francisco; Orazi, Maria Laura; Maritano Furcada, Joaquin (Medicina clinica, 2022)
Several reports have shown the persistence of long term symptoms after the initial COVID-19 infection (post-COVID-19 syndrome). The objective of this study was to analyze the characteristics of cardiopulmonary exercise testing (CPET) performed in patients with a history of COVID-19, comparing subjects according to the presence of post-COVID-19 syndrome. A cross-sectional study was performed. Consecutive patients >18 years with history of SARS-CoV-2 infection confirmed by polymerase chain reaction test and a CPET performed between 45 and 120 days after the viral episode were included. The association between variables related to CPET and post-COVID-19 syndrome was assessed using univariate and multivariate analysis. A total of 200 patients (mean age 48.8±14.3 years, 51% men) were included. Patients with post-COVID-19 syndrome showed significantly lower main peak VO (25.8±8.1mL/min/kg vs. 28.8±9.6mL/min/kg, p=0.017) as compared to asymptomatic subjects. Moreover, patients with post-COVID-19 syndrome developed symptoms more frequently during CPET (52.7% vs. 13.7%, p<0.001) and were less likely to reach the anaerobic threshold (50.9% vs. 72.7%, p=0.002) when compared to asymptomatic subjects. These findings were not modified when adjusting for confounders. Our data suggest that post-COVID-19 syndrome was associated with less peak VO , a lower probability of achieving the anaerobic threshold and a higher probability of presenting symptoms during the CPET. Future studies are needed to determine if these abnormalities during CPET would have prognostic value.